Discovery of Small Molecules that Induce the Degradation of Huntingtin. Issue 38 (9th August 2017) - Tomoshige, Shusuke; Nomura, Sayaka; Ohgane, Kenji; Hashimoto, Yuichi; Ishikawa, Minoru
Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by the aggregation of mutant huntingtin (mHtt), and removal of toxic mHtt is expected to be an effective therapeutic approach. We designed two small hybrid molecules (1 and2 ) by linking a ligand for ubiquitin ligase (cellular inhibitor of apoptosis protein 1; cIAP1) with probes for mHtt aggregates, anticipating that these compounds would recruit cIAP1 to mHtt and induce selective degradation by the ubiquitin‐proteasome system. The synthesized compounds reduced mHtt levels in HD patient fibroblasts and appear to be promising candidates for the development of a treatment for HD. Abstract : Hunting down huntingtin : Two small hybrid molecules consisting of a ligand for ubiquitin ligase linked with a probe for protein aggregates induce the selective degradation of aggregates of the huntingtin protein (Htt) by the ubiquitin‐proteasome system. These compounds are effective in reducing Htt levels in fibroblasts derived from Huntington's patients, and could open up a promising new approach for the development of drugs against Huntington's disease.